A proposed set of exercises on inference making designed for high school juniors - Latorilla, Nancy Dizon- 1931- (1977)
This paper presented forty sample exercises on inference making for third year high school students. Patterned after the Reading for Understanding series, these would be their local counterpart to be used by Junior students in developing differential skills. This paper also aimed to aid teachers in the field by providing them with a knowledge of the procedure in preparing materials that would develop the student's skill in getting the implied meaning of the printed word. The passages were lifted verbatim from the different sources but were revised thereafter to conform to the readability level in vocabulary lead and sentence length to the year level to which they are intended. Each exercise was also subjected to the Dale-Chall Readability Formula; the reading level of the students determined by the Gates Reading Survey- Form I; and for the item analysis, the high-low-27 percent-group method was used. The study revealed that the students were reading below par, grade levelwise, that they needed much training in comprehension skills, specially the inferential ones. Though they had the same reading level, they rated differently in the constructed exercises.
"May, 1977"
Vita.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Reading comprehension -- Problems, exercises, etc; Reading (Secondary) -- Philippines -- Problems, exercises, etc